Effect of Fe oxidation state (+2 versus +3) in precursor on the structure of Fe oxides/carbonates-based composites examined by XPS, FTIR and EXAFS - Chubar, Natalia; Gerda, Vasyl; Szlachta, Małgorzata; Yablokova, Ganna (Solid state sciences, 2021)
Here we investigate the influence of Fe oxidation state (either Fe(II) or Fe(III) sulfates) in precursor of the same chemical composition on the atomic scale structure, surface speciation and adsorptive anion removal of the purely inorganic composites produced under the urea supported hydrothermal synthesis. In case of utilization of Fe3+ precursor, the materials chemistry was solely dominated by the formation of highly crystalline Fe(III) oxides, however the particle surfaces were covered with small quantities of FeCO3 (not detectable by EXAFS/XANES/FTIR) precipitated after the autoclave was turned off. Within the reactive medium with Fe2+ precursor, due to high pressure in autoclave which facilitated reducing conditions and sedimentation of Fe divalent, two main processes took place one of which was the formation of Fe hydrous oxides; the second reaction resulted in generation of FeCO3, which become a predominant phase in volume averaged composition. Notably, despite the prevalence of Fe(II) carbonates in bulk structure, the narrow upper layers (XPS detectable) was enriched with Fe(III) oxides. At the chosen autoclave temperature of 150 °C, both samples had low hydration of physisorbed water, which confirmed our recent hypothesis about correlation between Fe (or another metal formed oxides) local structure in outer shells fitted with several (many) oxygen atoms and the material hydration with physisorbed water. None of the two composites demonstrated strong adsorptive removal of seven anions (F−, Br−, BrO3−, HAsO42−, H3AsO3, HPO42−, SeO42−), which verified another idea about the interdependence of distinguished (EXAFS simulated) outer shells of metals (here, Fe) fitted with two paths simultaneously (Fe–Fe+Fe–O) one peak and the anion exchange potential. Overall, the Fe(III)-precursor product was more crystalline, less heterogeneous (fewer phases), showed worse anion uptake than the other sample. The material prepared from Fe(II) precursor is considered to be a promising precursor for further phase transformations via thermal or hydrothermal treatments (due to generous presence of FeCO3). [Display omitted] •Two composites were produced hydrothermally from Fe(II) and Fe(III) precursors.•Bulk structure of Fe(II)-precursor-material was dominated by Fe carbonates.•Volume averaged Fe(III)-precursor-sample was formed upon Fe(III) oxides.•Surface speciation in both composites differed from their bulk compositions.•EXAFS simulated Fe local structure confirmed the recent methodological ideas.